Phosphate-sensing mechanisms and functions of phosphate as a first messenger - Yuichi Takashi (Endocrine Journal)
Bone secrets the hormone, fibroblast growth factor 23 (FGF23), as an endocrine organ to regulate blood phosphate level. Phosphate is an essential mineral for the human body, and around 85% of phosphate is present in bone as a constituent of hydroxyapatite, Ca10(PO4)6(OH)2. Because hypophosphatemia induces rickets/osteomalacia, and hyperphosphatemia results in ectopic calcification, blood phosphate (inorganic form) level must be regulated in a narrow range (2.5 mg/dL to 4.5 me/dL in adults). However, as yet it is unknown how bone senses changes in blood phosphate level, and how bone regulates the production of FGF23. Our previous data indicated that high extracellular phosphate phosphorylates FGF receptor 1 (FGFR1) in an unliganded manner, and its downstream intracellular signaling pathway regulates the expression of GALNT3. Furthermore, the post-translational modification of FGF23 protein via a gene product of GALNT3 is the main regulatory mechanism of enhanced FGF23 production due to high dietary phosphate. Therefore, our research group proposes that FGFR1 works as a phosphate-sensing receptor at least in the regulation of FGF23 production and blood phosphate level, and phosphate behaves as a first messenger. Phosphate is involved in various effects, such as stimulation of parathyroid hormone (PTH) synthesis, vascular calcification, and renal dysfunction. Several of these responses to phosphate are considered as phosphate toxicity. However, it is not clear whether FGFR1 is involved in these responses to phosphate. The elucidation of phosphate-sensing mechanisms may lead to the identification of treatment strategies for patients with abnormal phosphate metabolism.